An Evaluation of Stage One: The impact of introducing web-based learning technologies on post-secondary teaching and learning processes - MacSwain, V.; Mattock, D.; Robertson, W. (Proceedings of the International Conference on Networked Learning, 2000)
This paper describes stage one of the impact on learners, teachers and systems of implementing the WebCT course management tool in two very different post secondary institutions. The University of Prince Edward Island’s (UPEI) curricula are based on a very traditional course and program model. Holland College’s curricula are based on modules and skills development. The research evaluates hos each institution implements WebCT as a curriculum development and delivery tool in which Web components will be selectively employed to give learners more independence and teachers increased options in how to schedule and teach. How both institutions adapt their infrastructures to accommodate WebCT is evaluated.